Implementasi Kebijakan Penertiban Ternak di Kecamatan Pante-Makassar, Oe-Cusse, Timor Leste - Victor Manuel Neno; Hartuti Purnaweni; Ida Hayu Dwimawanti; Teuku Afrizal (Mahesa Research Center, 2022)
This study focuses on the Implementation of Livestock Control in the District of Pante-Makassar, Oe-Cusse, Timor Leste, this study aims to analyze the extent to which the Implementation of Livestock Control Policies in the District of Pante-Makassar, Oe-Cusse, Timor Leste, and the supporting and inhibiting factors of implementation Policy. The methodology used in this paper is a descriptive qualitative method. This research uses selected informants by purposive sampling. There are 10 informants in this research. The method used in gathering information is observation, interviews and documentation. The results of the study indicate that human resources and financial resources, when viewed from these two resources, it can be concluded that there is a lack of human resources and financial resources that are still minimal so that it can affect the implementation of livestock management policies. In the disposition there is a consensus between policy makers and policy implementers. The organizational structure of livestock control has been established and has carried out its duties but in its implementation it has not been as expected in accordance with the government decree that has been set. the government needs to pay attention to financial resources and human resources so that before implementing policies. It is necessary to conduct socialization to livestock owners before the policy is implemented.